Meningkatkan Hasil Belajar Pakat Melalui Model PBL pada Siswa SD Negeri Kutowinangun 08 Salatiga - Setiono Setiono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research aims to determine the improvement of cognitive and affective learning outcomes in the dimensions of faith in God Almighty and Mutual Cooperation through the PBL model for students at SD Negeri Kutowinangun 08. This type of research is classroom action research with research steps including planning, implementation, observation, and reflection in each cycle. This study consists of two cycles. The research location is SD Negeri Kutowinangun 08 Salatiga, focusing on fourth-grade students with the material "Ten Commandments of God as Life Guidelines". The research was conducted in September 2024. Data collection techniques used learning outcome tests and affective observation rubrics. The data analysis technique used is descriptive quantitative. From the research results, there is an increase in cognitive learning outcomes by 20% in the Proficient criteria and 5% in the Competent criteria. Affective learning outcomes using the PBL learning model have been proven to improve students' affective learning outcomes at SD Negeri Kutowinangun 08 Salatiga on the material "Ten Commandments of God as Life Guidelines". The improvement can be seen from the number of students in cycle I, where 100% fell into the Competent criteria, and in cycle II there was a significant change with 100% falling into the Proficient criteria.